WHEN SHOULD BE CONVERTED LAPAROSCOPIC SLEEVE GASTRECTOMY TO LAPAROSCOPIC ROUX-EN-Y GASTRIC BYPASS DUE TO GASTROESOPHAGEAL REFLUX? - BRAGHETTO,Italo (2020)
ABSTRACT Background: Gastroesophageal reflux (GER) is one of the most common indications for conversion of sleeve gastrectomy (LSG) to laparoscopic Roux-en-Y gastric bypass (LRYGBP). Objective evaluations are necessary in order to choose the best definitive treatment for these patients. Aim: To present and describe the findings of the objective studies for gastroesophageal reflux disease performed before LSG conversion to LRYGBP in order to support the indication for surgery. Method: Thirty-nine non-responder patients to proton pump inhibitors treatment after LSG were included in this prospective study. They did not present GER symptoms, esophagitis or hiatal hernia before LSG. Endoscopy, radiology, manometry, 24 h pH monitoring were performed. Results: The mean time of appearance of reflux symptoms was 26.8+24.08 months (8-71). Erosive esophagitis was found in 33/39 symptomatic patients (84.6%) and Barrett´s esophagus in five. (12.8%). Manometry and acid reflux test were performed in 38/39 patients. Defective lower esophageal sphincter function was observed independent the grade of esophagitis or Barrett´s esophagus. Pathologic acid reflux with elevated DeMeester´s scores and % of time pH<4 was detected in all these patients. more significant in those with severe esophagitis and Barrett´s esophagus. Radiologic sleeve abnormalities were observed in 35 patients, mainly cardia dilatation (n=18) and hiatal hernia (n=11). Middle gastric stricture was observed in only six patients. Conclusion: Patients with reflux symptoms and esophagitis or Barrett´s esophagus after SG present defective lower esophageal sphincter function and increased acid reflux. These conditions support the indication of conversion to LRYGBP.